2022
DOI: 10.3390/microorganisms10112243
|View full text |Cite
|
Sign up to set email alerts
|

Report and Comparative Genomics of an NDM-5-Producing Escherichia coli in a Portuguese Hospital: Complex Class 1 Integrons as Important Players in blaNDM Spread

Abstract: Background: New Delhi metallo-beta-lactamase (NDM) has been spreading across the globe, but the causes of its success are poorly understood. We characterized a blaNDM-5-positive Escherichia coli strain from a Portuguese hospital and conducted comparative genomic analyses to understand the role of clonal background and horizontal gene transfer in blaNDM-5 dissemination. Methods: After blaNDM PCR screening and genome sequencing, Ec355340 was subjected to mating, transformation, and plasmid curing assays and MICs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…These evidence collectively suggest that the bla NDM-5 -carrying cassette is frequently transferred as an integral complex with class 1 integron rather than as a standalone gene cassette, as also implicated in previous studies with E. coli. 47,48 Nevertheless, future research is necessary to validate the role of class 1 integron and ISCR1 element in the dissemination of bla NDM-5 gene. Using cgSNP-based phylogenetic analysis, we found that A132 shares a close genomic relationship with numerous Chinese S. London ST155 strains retrieved from EnteroBase.…”
Section: Discussionmentioning
confidence: 99%
“…These evidence collectively suggest that the bla NDM-5 -carrying cassette is frequently transferred as an integral complex with class 1 integron rather than as a standalone gene cassette, as also implicated in previous studies with E. coli. 47,48 Nevertheless, future research is necessary to validate the role of class 1 integron and ISCR1 element in the dissemination of bla NDM-5 gene. Using cgSNP-based phylogenetic analysis, we found that A132 shares a close genomic relationship with numerous Chinese S. London ST155 strains retrieved from EnteroBase.…”
Section: Discussionmentioning
confidence: 99%